Teoria crítica da informação: teoria crítica em Ciência da Informação no caminho da Escola de Frankfurt - Cavalcante, Anderson Victor Barbosa (2023)
This study aims to understand the Frankfurt Critical Theory as a philosophicalsociological foundation for the construction of a Critical Theory of Information. Conducts a study classified as theoretical, of an epistemological nature, in the bachelardian perspective, and subsidized by hermeneutics, in the habermasian perspective. In view of its general objective, the study raises five specific objectives. First, it identifies the main conceptual categories discussed by Max Horkheimer in his Critical Theory (also known as Critical Theory of the Frankfurt School), namely, Traditional Theory and Critical Theory. Second, it relates Traditional Theory and Critical Theory respectively to Mathematical Theory of Information and Critical Theory of Information, valid theories in Information Science. Third, it discusses the “place” of the Critical Theory tradition within Applied Social Sciences, notably in the context of Information Science. Fourth, it recognizes the role and significance of Critical Theory as a philosophicalsociological foundation of profound relevance to contemporary thinking in Information Science. And, finally, fifth, it develops a concept proposition for a Critical Theory of Information for the field of Information Science, based on the outlines of the Frankfurt Critical Theory. Along these lines, it discusses two distinct visions of theory, of science, of the world. On the one hand, it discusses the character of a Critical Theory of Information as a locus in which information and the field of information assume the mission of a vector of reflection, criticism and self-criticism, as a motivating force for actions and intimate and collective changes for subjects and societies, as a phenomenon that articulates social evolution and collective well-being. On the other hand, it discusses the character of a purely Mathematizable Theory of Information as a locus in which information and the field of information assume the condition of a clearly technicist, physicalist and functional vector, forged by the ends of the market and the systemic order, as a profoundly useful and efficient to the demands of the instrumental/capital order. It concludes that the configuration of a scenario focused on the purely mathematizable/capitalized/instrumental character of information and the field of information clouds and hinders the understanding and perception of the phenomenon of information and the informational field in terms of its civilizing, humanistic, emancipatory projections, while Social Science. It ends by defending the validity of the Critical Theory referrals in the informational field as a motivating path to conceive and perceive Information Science, information and field things in more critical-reflexive, dialectical, dialogical, humanistic and emancipatory terms, so that to reaffirm its belonging to the condition of Social Science, far beyond pragmatist, technical and purely positivist projections.